Copula-based Bivariate Cointegration Model. Issue 1 (May 2019) - John, Nimitha; Balakrishna, N.
This article focuses on a bivariate cointegrating model with non-normal errors. In particular, we propose a bivariate error distribution constructed using two non-identical marginals through a copula. The model parameters are estimated using the method of inference functions for margins and maximum likelihood. Applications of the proposed model are illustrated through real life examples. AMS classification codes: 62M10